2019
DOI: 10.1097/scs.0000000000005460
|View full text |Cite
|
Sign up to set email alerts
|

Median Perforating Canal in Human Mandible

Abstract: Surgical interventions in the anterior region of the human mandible are associated with many complications. Some anatomical structures like the median perforating canal were discovered in mammals. Such canals may be a cause of concern that needs attention in human mandible. The purpose of the present study was to evaluate the occurrence, location, and course of median perforating canal and its associated extensions in the anterior segment of the human mandible in cone beam computed tomography scans (CBCT). Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Multiple cadaver studies consistently found that 64%-99.7% of individuals had a median lingual foramen [15][16][17][18][19][20][21] . By gross anatomy, the lateral foramen of the tongue contains a branch of the submental artery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Multiple cadaver studies consistently found that 64%-99.7% of individuals had a median lingual foramen [15][16][17][18][19][20][21] . By gross anatomy, the lateral foramen of the tongue contains a branch of the submental artery.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that the distance from the median lingual foramen to the alveolar ridge is 4.73-24.43 mm, and the average distance is 15.49 mm. The diameter range of the lingual foramen is 0.18-1.8 mm [15][16][17][18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on cadavers have shown that branches from the sublingual and/or submental arteries go through these anatomic structures. Therefore, despite being generally considered as a safe area during performing surgical procedures, this mandibular region may present a real lifethreatening hemorrhage from the above cited arterial branches following the lingual cortical plate trauma ( 26,27,20 .…”
Section: Introductionmentioning
confidence: 99%